2016
DOI: 10.1111/evj.12630
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dose and diet on the pharmacodynamics of omeprazole in the horse

Abstract: The overall efficacy of omeprazole in raising ventral gastric pH was less than previously reported. Both dose and diet may play a role in the efficacy of omeprazole in the horse. Therefore, the use of singular dosing recommendations that encompass all horse types and management conditions may not be appropriate and dosing recommendations that take into account the diet of the horse may be advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 31 publications
7
47
1
Order By: Relevance
“…A similar effect has been reported in human subjects when intragastric pH is measured in multiple locations . It is unclear which measurement location more accurately reflects healing conditions at the level of the mucosa, but it has been proposed previously that measurement location 1 may be more predictive as it is fixed in a known position 10–20 mm from the glandular mucosa, and the level of acid suppression reported at measurement location 1 in a previous study evaluating omeprazole correlates well with reported healing rates in clinical trials for the doses studied. By contrast, the exact location of the tip of the probe, and thus of measurement location 2, is not known but it can reasonably be expected to be buried in the ingesta .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A similar effect has been reported in human subjects when intragastric pH is measured in multiple locations . It is unclear which measurement location more accurately reflects healing conditions at the level of the mucosa, but it has been proposed previously that measurement location 1 may be more predictive as it is fixed in a known position 10–20 mm from the glandular mucosa, and the level of acid suppression reported at measurement location 1 in a previous study evaluating omeprazole correlates well with reported healing rates in clinical trials for the doses studied. By contrast, the exact location of the tip of the probe, and thus of measurement location 2, is not known but it can reasonably be expected to be buried in the ingesta .…”
Section: Discussionsupporting
confidence: 74%
“…In an earlier report using a similar model, and studying horses consuming ad libitum roughage supplemented with a grain meal twice per day, a commercial buffered paste formulation of omeprazole achieved a pH>4 for only 14 h and 11 h on days 2 and 7 of treatment, respectively, even at the registered treatment dose of 4 mg/kg bwt by mouth once per day . Similarly, a recent report evaluating the effectiveness of the same commercial paste, and similarly using a dose of 4 mg/kg bwt by mouth once per day in horses consuming ad libitum roughage, reported %tpH>4 values on day 5 of approximately 40% and 30% for measurement locations 1 and 2, respectively .…”
Section: Discussionmentioning
confidence: 88%
“…The results of the current study suggest that, although not consistent across all dose‐diet interactions studied, both dose and diet may play a role in the efficacy of esomeprazole in the horse. A similar finding has recently been reported for omeprazole in the horse . The findings of the present study further support the idea that the use of singular dosing recommendations for oral PPIs that encompass all horse types and usages, with their associated differences in management, may not be appropriate.…”
Section: Discussionsupporting
confidence: 90%
“…() showed a more pronounced effect using an oral paste formulation of omeprazole at 4 mg/kg, which inhibited both basal and pentagastrin‐stimulated gastric acid secretion by 99% at 5–8 hr after treatment and by 83% (basal) and 90% (pentagastrin‐stimulated) at 21–24 hr. Sykes, Underwood, Greer, McGowan, and Mills () have shown that dose and diet affect the response to omeprazole in the horse in an inconsistent manner. Clearly, there are several factors that influence the duration of effect of omeprazole which is not surprising given the fact it is a quasi‐irreversible inhibitor of H + /K + ‐ATPase.…”
Section: Discussionmentioning
confidence: 99%